Utilization of transition metal fluoride-based solid support catalysts for the synthesis of sulfonamides: carbonic anhydrase inhibitory activity and in silico study. Issue 5 (24th January 2022) - Ali, Deedar; Amjad, Sayyeda Tayyeba; Shafique, Zainab; Naseer, Muhammad Moazzam; al-Rashida, Mariya; Sindhu, Tayyaba Allamgir; Iftikhar, Shafia; Shah, Muhammad Raza; Hameed, Abdul; Iqbal, Jamshed
Abstract : The applications of solid support catalysts in catalyzing organic reactions are well-evident. Abstract : The applications of solid support catalysts in catalyzing organic reactions are well-evident. In the present study, we explored a transition metal fluoride (FeF3 ) adsorbed on molecular sieves (4 Å) as a solid support catalyst for the preparation of sulfonamides 3a–3o . The solid support catalyst was characterized via X-ray diffraction and AFM analysis. The catalyst was further explored for the synthesis of indoles 6a–h, 1H-tetrazoles and 1, 4-dihydropyridines. The sulfonamides prepared herein were investigated for their potential to inhibit carbonic anhydrase (hCA II, hCA IX and hCA XII). All compounds were found to be active inhibitors with IC50 values in the low micromolar range. Some compounds were even found to be highly selective inhibitors. Compound 3i only inhibited hCA II (IC50 = 2.76 ± 1.1 μM) and had <27% inhibition against hCA IX and hCA XII. Similarly, 3e (IC50 = 0.63 ± 0.14 μM) only inhibited hCA XII and showed <31% inhibition against hCA II and hCA IX. Molecular docking studies were carried out to rationalize the ligand-binding site interactions. Given the lack of selective CA inhibitors, compounds 3e and 3i can provide significant leads for the further development of highly selective CA inhibitors.